Impact of chemotherapeutic agents on the immunostimulatory properties of human 6-sulfo LacNAc+ (slan) dendritic cells - Wehner, Rebekka; Bitterlich, Anna; Meyer, Nicole; Kloß, Anja; Schäkel, Knut; Bachmann, Michael; Schmitz, Marc (International journal of cancer, 2013)
Chemotherapy is an important treatment modality for many patients with advanced cancer. Recent data revealed that certain chemotherapeutic agents differentially affect maturation, cytokine production and T-cell stimulatory capacity of dendritic cells (DCs), which play a crucial role in the induction of antitumor immunity. Whereas most reports are based on mouse or human monocyte-derived DCs, studies investigating the direct effect of chemotherapeutic drugs on native human DCs are rather limited. Here, we evaluated the impact of various chemotherapeutic drugs on the immunostimulatory properties of 6-sulfo LacNAc+ (slan) DCs, representing a major subpopulation of human blood DCs. Because of their various antitumor effects, slanDCs may essentially contribute to the immune defense against tumors. We demonstrated that doxorubicin and vinblastine significantly impair the release of tumor necrosis factor-α, interleukin (IL)-6 and IL-12 by slanDCs. Functional data revealed that both drugs inhibit slanDC-mediated proliferation of T lymphocytes and their capacity to differentiate naive CD4+ T cells into proinflammatory T-helper type I cells. Furthermore, these agents markedly suppressed the ability of slanDCs to stimulate interferon-γ secretion by natural killer (NK) cells. In contrast, paclitaxel, mitomycin C and methotrexate sustained the ability of slanDCs to produce proinflammatory cytokines and their potential to activate T-lymphocytes and NK cells. These results indicate that doxorubicin and vinblastine impair the ability of native human DCs to stimulate important immune effector cells, whereas methotrexate, mitomycin C and paclitaxel maintain their immunostimulatory properties. These novel findings may have implications for the design of treatment modalities for tumor patients combining immunotherapeutic strategies and chemotherapy.
Online 21 Aug 2012
Im Titel ist "+" hochgestellt
Gesehen am 18.10.2021